Developing contextual learning videos on energy transformation for elementary students - Herlina Herlina; Degi Alrinda Agustina; Dedi Kusnadi; Agustinus Toding Bua; Andi Ard Maidhah; Sucahyo Mas'an Al Wahid (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
The use of learning media can attract students' interest in learning, increase motivation and make it easier to understand the material. This research aims to develop learning video media with a feasible and interesting contextual approach. This research is a Research and Development with the flow of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection instruments used were in the form of validation sheets and student response questionnaires. This research was conducted in class IV C SDN 006 Tarakan. The results of the validation of material experts were obtained at 80%, including the feasible category, media experts were obtained at 88.33% including the very feasible category, linguists were obtained at 83.13% including the very feasible category. The results of the limited trial student response were obtained of 82.54%, including the very interesting category, and the results of the field trial student response were obtained of 89.72%, including the very interesting category. Based on the results of the validation of materials, media and language, as well as student response questionnaires in limited trials and field trials, learning videos with a contextual approach were declared feasible and interesting to be used in the learning process.